Orthodontic Treatment of Impacted Canines - Mete Özer; Mehmet Bayram (Galenos Yayinevi, 2005)
Maxillary canines have the longest period of development, the deepest area of development, and the most difficult path of eruption of all the teeth. Other than the third molars, the maxillary canines are the most likely to remain unerupted or impacted. They are also the teeth that most commonly require s u rgical exposure and orthodontic guidance during eruption. Maxillary canine impactions are more common in females (1,17%) than in males (0,51%). The frequency of maxillary canine impaction is significantly higher than that of mandibular canines. Impacted maxillary canines are also situated palatally more frequently than labially. 7% of the patients with impacted maxillary canines have bilateral impactions. The ectopic eruption and impaction of maxillary permanent canines is a frequently encountered clinical problem. The diagnosis and treatment of this problem usually requires the expertise and cooperation of the general practitioner, the pediatric dentist, the oral surgeon and the periodontist, as well as the orthodontist. During the last decade different ways for treatment of this problem have been suggested. This case report discusses the orthodontic treatment approaches for the management of impacted canines using different techniques in two impacted canine cases.